1094. Determination of Plasma Protein Binding of Dalbavancin. (4th December 2021) - Turner, Nicholas A; Xu, Allan; Zaharoff, Smitha; Holland, Thomas L; Holland, Thomas L; Lodise, Thomas; Lodise, Thomas
Abstract: Background: Dalbavancin is a semi-synthetic glycopeptide with a long half-life, making it a promising alternative for infections requiring prolonged therapy such as complicated Staphylococcus aureus bacteremia. A critical pharmacokinetic consideration with prolonged treatment is the unbound or "free" concentration-time profile, as f ree antibiotic concentrations may correlate with tissue penetration and therapeutic effects better than total drug . Dalbavancin's plasma protein binding (PB) remains poorly studied and has been reported to range between 93-99%. A reliable and validated free drug assay is needed to link dalbavancin concentrations with patient outcomes. Methods: The ultracentrifugation technique was used to determine free dalbavancin concentrations in plasma at two concentrations (50 and 200 µg/mL) in duplicate. Centrifuge tubes and pipette tips were treated for 24 hours before use with Tween 80 to assess adsorption. PB centrifugation conditions: 400, 000 g (106, 000 RPM in TLA-120.1 rotor) for 4 hours at 37°C. Dalbavancin concentrations were analyzed from the plasma samples (total) and middle layer samples (free) by liquid chromatography – tandem mass spectrometry (LC/MS/MS) with isotopically labeled internal standard. Warfarin served as a positive control with known high protein binding. Results: Measurement of free dalbavancin was sensitive to adsorption onto plastic. Treatment of tubes and pipette tips with ≥2% Tween 80 effectively prevented drug loss during PB experiments (Figure 1). Addition of 2% Tween 80 did not affect PB results of warfarin. In PB experiments with 2% Tween 80 coated tubes, the free fraction of dalbavancin was 0.96% (95% CI: 0.94-0.98) at 50 µg/mL and 1.11% (95% CI: 1.08-1.13) at 200 µg/mL. Figure 1. Percent Free Dalbavancin vs Varying Concentrations of Tween 80 for Pretreatment of Tubes Conclusion: By the ultracentrifugation method, dalbavancin's PB was estimated to be approximately 99%. Given dalbavancin's high PB, accurate measurement of free dalbavancin concentrations should be a key consideration in future exposure-response studies, especially clinical trials. Future investigations should also determine if the active fraction is best predicted by the free or total fraction, as this remains a subject of debate. Supported by NIAID/NIH grant UM1AI104681. Content is solely the authors' responsibility and does not represent official NIH views. Disclosures: Thomas L. Holland, MD, Aridis (Consultant)Basilea Pharmaceutica (Consultant)Lysovant (Consultant) Thomas L. Holland, MD, Aridis (Individual(s) Involved: Self): Consultant; Basilea Pharmaceutica (Individual(s) Involved: Self): blinded adjudication, Consultant, Other Financial or Material Support; Genentech (Individual(s) Involved: Self): Consultant; Lysovant (Individual(s) Involved: Self): Consultant; Motif Bio (Individual(s) Involved: Self): Consultant Thomas Lodise, Jr., PharmD, PhD, Astra-Zeneca (Consultant)Bayer (Consultant)DoseMe (Consultant, Advisor or Review Panel member)ferring (Consultant)genentech (Consultant)GSK (Consultant)Melinta (Consultant)merck (Consultant, Independent Contractor)nabriva (Consultant)paratek (Consultant, Advisor or Review Panel member, Speaker's Bureau)shionogi (Consultant, Advisor or Review Panel member, Speaker's Bureau)Spero (Consultant)tetraphase (Consultant)Venatrox (Consultant) Thomas Lodise, Jr., PharmD, PhD, Melinta Therapeutics (Individual(s) Involved: Self): Consultant; Merck (Individual(s) Involved: Self): Consultant, Scientific Research Study Investigator; Paratek (Individual(s) Involved: Self): Consultant; Shionogi (Individual(s) Involved: Self): Consultant, Speakers' bureau; Spero (Individual(s) Involved: Self): Consultant; Tetraphase Pharmaceuticals Inc. (Individual(s) Involved: Self): Consultant